Possible effects of repeated exposure to ibuprofen and acetaminophen on the intestinal immune response in young infants. (February 2016) - Langhendries, J.-P.; Allegaert, K.; Van Den Anker, J.N.; Veyckemans, F.; Smets, F.
Abstract: There has been an exponential increase in the frequency of immune deviations in young children. Consequently, research investigating environmental causes for this increase has become a Public Health priority. We have summarized the experimental observations and epidemiological data that could link repeated acetaminophen and ibuprofen exposure in early infancy to this increase. Recent observations on the maturational immunity of the intestinal sub-mucosal lamina propria underscore indeed the importance of prostaglandins (PGE2s). PGE2 appearing at this sub-mucosal level is a product of arachidonic acid metabolism mediated by type-2 cyclooxygenase (COX-2) situated on the membrane of many immune cells. Moreover, it seems that acetaminophen – like ibuprofen – also carries a non-selective inhibitory action on peripheral COXs, besides its central action. This inhibitory action of acetaminophen on COX2 only relates to physiological, low arachidonic acid concentrations. This explains the difference in anti-inflammatory effects. The impact of repeated inhibition of mucosal PGE2 synthesis due to COX-inhibitor exposure on maturational immunity has been demonstrated in animal experiments. Repeatedly exposed young animals do not develop tolerance to food antigens and exhibit autoimmune deviations. Several recent epidemiological studies have also reported on the magnitude of acetaminophen and ibuprofen exposure in children and the increase in immune deviations, it is important to better understand the potential negative impact of repeated inhibitions of prostaglandin synthesis by COX2s during infancy. Since acetaminophen and ibuprofen are commonly administered analgesics and antipyretics, a well-designed prospective strategy for pharmacovigilance and -epidemiology of COX-inhibitor exposure in infancy is urgently needed.